The knowledge of primary health care professionals regarding mental health: diagnosis by mhGAP - Joana Moscoso Teixeira de Mendonça; Ilana Eshriqui; Leticia Yamawaka de Almeida; Valmir Vanderlei Gomes Filho; Lívia Schunk; Ana Alice Freire de Sousa; Larissa Karollyne de Oliveira Santos; Sandra Fortes (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To analyze knowledge about priority topics in mental health care of strategic actors who work in regions where the Health Care Planning (PAS) methodology is used. METHODS This is a quantitative, descriptive, cross-sectional, and observational study carried out with professionals from six health regions, distributed in three Brazilian states (Goiás, Rondônia and Maranhão) and linked to the project "Saúde mental na APS" (Mental health in PHC) of the Programa de Apoio ao Desenvolvimento Institucional do Sistema Único de Saúde (Proadi-SUS - Institutional Development Support Program of the Brazilian Unified Health System). The sample was made up of professionals who participated in the intervention guide multiplier training stage for mental, neurological and alcohol and other drug use disorders in the primary health care network, from July to September 2022. Data collection was through a self-administered instrument, in electronic format, consisting of a block with socioeconomic items and a structured questionnaire to assess participants' knowledge about priority topics in mental health. Descriptive analyses and comparison of proportions were conducted to analyze the data. RESULTS A total of 354 health professionals participated in the study. Regarding the percentage of correct answers in the questionnaire on priority topics in mental health, the highest medians were identified in the "Depression" module. On the other hand, the content referring to the modules "Essential care and practices" and "Other important complaints" presented the lowest values. Furthermore, some participant characteristics were found to be associated with the percentage of correct answers in the questionnaire modules. CONCLUSIONS The findings reveal opportunities for improvement, mainly in knowledge related to communication skills and the approach to emotional and physical distress without diagnostic criteria for a specific disease, offering support for planning actions aimed at intensifying the consideration of these themes during the operational stages of PAS.